Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak: Studi KPP Kota Semarang - Nurcahyono, Nurcahyono; Subkhi, Muhammad; Hardiwinoto, Hardiwinoto (COMPETITIVE, 2021)
This study aims to determine the effect of tax socialization, fiscal service, tax awareness, and tax sanctions on obedience of personal taxes obligatory. This research was conducted at the East Semarang Primary Tax Office. The number of samples taken is 100 taxpayers. The sampling technique used is convienance Sampling or sampling based on convienance. Data were analyzed using multiple linear regression analysis. Based on the results of the study showed that the tax socialization, fiscal service, tax awareness, and tax sanctions had a positive effect on obedience of personal taxes obligatory at East Semarang Primary Tax Office. The results showed that the tax socialization, fiscal service, tax awareness, and tax sanctions policy could increase taxpayer compliance at the East Semarang Primary Tax Office